Design Of WEB-Based Accounting And Tax Information Systems At UMKM Rumah Sehat MKK Bersinar - Nurlela, Nurlela; Eka Triayuningsih; Adithya Pratama (Jurnal Ekonomi, 2024)
Information technology is one of the competitive advantages of MSMEs. Information technology provides convenience in work activities and provides accurate and effective financial information. Accounting and tax information system is a form of business information technology development in the field of accounting and tax that produces information in the form of financial statements and accurate tax calculations, so that it can be used as a tool in increasing the trust of creditors and tax institutions. However, MSMEs, especially MSMEs Rumah Sehat MKK Bersinar do not have an accounting and tax information system, so they do not have financial statements and tax calculations for MSMEs. The same condition experienced by UMKM rumah sehat MKK bersinar does not have an accounting and Tax Information System System that is able to provide convenience to owners to record transactions and taxes, control assets so as to produce accurate financial statements and tax calculations. Accounting and tax information systems are designed using web-based software databases that XAMPP supported program suport Apache, MySQL, and PHP with the method through the method Framework the Application of System Thinking. Data collection techniques through observation and interviews. Based on the results of research, the accounting information system designed must be in accordance with the workflow of MSME rumah sehat MKK bersinar, system users, user tasks and information needs by the owner. In addition, the system is designed in accordance with the EMKM SAK which applies the accrual recording method. Accounting and tax information systems provide convenience to rumah sehat MKK bersinar in conducting accounting activities and generating financial and tax reports.